The Development of the Digital Identification Instrument for Children with Learning Disabilities using Decision Support System (DSS) - Rejeki, Dewi Sri; Supratiwi, Mahardika; Subagya, Subagya; Kumalasari, Erma (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The study is a part of research and development which aims at developing Decision Support System-based (DSS) digital identification instrument for children with learning disabilities. The first-year study consists of three stages: (a) the need analysis of the instrument, (b) the development of instrument prototypes, and (c) the validation of the digital identification instrument. The study was conducted in Surakarta, particularly in 20 special schools located in 7 regencies and cities and selected using purposive sampling. In the first stage, data were collected using a close-ended questionnaire from 32 respondents comprising principals and teachers. Meanwhile, the second stage use of a web-based digital application development technique. The identification instrument was then validated through expert judgment using focus group discussion (FGD) technique involving information and technology (IT) experts, special education experts, principals, and teachers of children with learning disabilities. The instrument prototypes were subsequently revised and limited empirical tryout, and then analyzed using statistical tests. The results indicate that 97% of the respondents require the development of a digital identification instrument for children with learning disabilities. The study has successfully developed digital identification instrument prototypes for children with learning disabilities. All items of the DSS-based instrument have met the required criteria of validity: r-table with the number of subjects of 32, a significance level of 5% (0.361), and greater r-count compared to r-table (0.361). The reliability tests demonstrate Cronbach's alpha of 0.875. It's proved that 13 items of the instrument have a sufficient level of reliability.